2007
DOI: 10.3354/dao074067
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a rediscovered haplosporidian parasite from cultured Penaeus vannamei

Abstract: Mortalities of Penaeus vannamei, cultured in ponds in Belize, Central America, began during the last part of the grow-out cycle during the cold weather months from September 2004 through February 2005. Tissue squashes of infected hepatopancreata and histological examination of infected shrimp revealed that the mortalities might have been caused by an endoparasite. To confirm the diagnosis, DNA was extracted from ethanol preserved hepatopancreata and the small-subunit rRNA gene was sequenced. The 1838 bp sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The relationship of the crab parasite to existing members of the genus Haplosporidium is somewhat surprising given that other known haplosporidian parasites from marine crustaceans, including those from the Pacific white shrimp Litopenaeus vannamei (Nunan et al 2007, Utari et al 2012) and particularly another from the spot prawn Pandalus platyceros (Reece et al 2000), were shown to be phylogenetically dissimilar to H. littoralis from European crabs. Despite the rather limited literature on this subject, the relatively wide variation in SSU rDNA gene sequence among these 3 parasites is suggestive of an underlying diversity in the as-yet undiscovered haplosporidian fauna in fecting crustacean hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of the crab parasite to existing members of the genus Haplosporidium is somewhat surprising given that other known haplosporidian parasites from marine crustaceans, including those from the Pacific white shrimp Litopenaeus vannamei (Nunan et al 2007, Utari et al 2012) and particularly another from the spot prawn Pandalus platyceros (Reece et al 2000), were shown to be phylogenetically dissimilar to H. littoralis from European crabs. Despite the rather limited literature on this subject, the relatively wide variation in SSU rDNA gene sequence among these 3 parasites is suggestive of an underlying diversity in the as-yet undiscovered haplosporidian fauna in fecting crustacean hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Several apparently asporous haplosporidian-like pathogens have also been described infecting crustacean hosts, including blue crabs Callinectes sapidus from the USA (Newman et al 1976); spot prawns (Pandalus spp.) from the coasts of Alaska and western Canada (Meyers et al 1994, Bower & Meyer 2002, Hine et al 2009); European shore crabs Carcinus maenas from British waters (Stentiford et al 2004); and farmed Litopenaeus vannamei from Central America and Asia (Dyková et al 1988, Nunan et al 2007, Utari et al 2012. Spore-forming haplosporidians of crustaceans have been described infecting the decapod Rhithro panopeus harrisii tridentatus (Marchand & Sprague 1979) and re cently from freshwater amphipods of the genus Diporeia (Messick 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The losses since 2007 have been estimated at approximately US$5 million. The gross signs of disease and histopathology caused by the parasite resembled those previously described from the Americas (Dyková et al, 1988;Nunan et al, 2007), and sequences of PCR-amplified rRNA sequences shared 96% identity with those form the American report. Given the 4% difference in sequence identity, it is uncertain whether the parasite is a variant of the previously described American species or a new species.…”
Section: Overview Of New and Major Non-viral Pathogens In Asiamentioning
confidence: 53%
“…and Minchinia spp. The relationship with the latter and H. costale has recently been supported in phylogenies based on actin gene sequences (López-Flores et al 2007), and on a prawn haplosporidian (Nunan et al 2007). Future studies may confirm the placing of crustacean haplosporidians close to or between Bonamia spp.…”
Section: Haplosporogenesismentioning
confidence: 69%
“…(Comps & Tigé 1997) in different families of bivalves. H. louisiana is a parasite of decapods that, unlike other known haplosporidians of crustaceans (Newman et al 1976, Dyková et al 1988, Bower & Meyer 2002, Stentiford et al 2004, Nunan et al 2007), forms spores. Observations on the other crustacean haplosporidians suggest that, for at least part of their life-cycles, they form large multi-nucleate plasmodia that internally divide to form uni-nucleate bodies, which separate and undergo karyokinesis to form multi-nucleate plasmodia, and the cycle is repeated.…”
Section: Phylogenetic Patterns In Relation To the Taxonomy Of Host Spmentioning
confidence: 99%